Vaccine development: obligate intracellular bacteria new tools, old pathogens: the current state of vaccines against obligate intracellular bacteria - van Schaik, E. J.; Fratzke, A. P.; Gregory, A. E.; Dumaine, Jennifer E.; Samuel, J. E. (Frontiers in Cellular and Infection Microbiology, 2024)
Obligate intracellular bacteria have remained those for which effective vaccines are unavailable, mostly because protection does not solely rely on an antibody response. Effective antibody-based vaccines, however, have been developed against extracellular bacteria pathogens or toxins. Additionally, obligate intracellular bacteria have evolved many mechanisms to subvert the immune response, making vaccine development complex. Much of what we know about protective immunity for these pathogens has been determined using infection-resolved cases and animal models that mimic disease. These studies have laid the groundwork for antigen discovery, which, combined with recent advances in vaccinology, should allow for the development of safe and efficacious vaccines. Successful vaccines against obligate intracellular bacteria should elicit potent T cell memory responses, in addition to humoral responses. Furthermore, they ought to be designed to specifically induce strong cytotoxic CD8+ T cell responses for protective immunity. This review will describe what we know about the potentially protective immune responses to this group of bacteria. Additionally, we will argue that the novel delivery platforms used during the Sars-CoV-2 pandemic should be excellent candidates to produce protective immunity once antigens are discovered. We will then look more specifically into the vaccine development for Rickettsiaceae, Coxiella burnetti, and Anaplasmataceae from infancy until today. We have not included Chlamydia trachomatis in this review because of the many vaccine related reviews that have been written in recent years.